2019
DOI: 10.1103/physrevfluids.4.034603
|View full text |Cite
|
Sign up to set email alerts
|

Importance of small-scale anisotropy in the turbulent/nonturbulent interface region of turbulent free shear flows

Abstract: There has been much debate over the past decade or so over the scaling of the thickness of the turbulent/nonturbulent (TNT) interface for turbulent shear flows. It is generally considered to consist of the outer viscous superlayer, in which viscous processes are significant, and an inner turbulent sublayer which is dominated by inertial processes. Various authors have stated that the interface thickness scales with the Taylor length scale λ whilst others state that it scales with the Kolmogorov length scale η.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…The no-grid case, as described by run 1a, produces results that are similar to those of Buxton et al. (2019), with an increase in anisotropy being observed near the wake boundary on the wake side of the interface. A very gradual increase in the anisotropy ratio is also observed on the free-stream side of the wake boundary, however, the magnitude of this increase in not comparable to the behaviour inside the wake.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The no-grid case, as described by run 1a, produces results that are similar to those of Buxton et al. (2019), with an increase in anisotropy being observed near the wake boundary on the wake side of the interface. A very gradual increase in the anisotropy ratio is also observed on the free-stream side of the wake boundary, however, the magnitude of this increase in not comparable to the behaviour inside the wake.…”
Section: Resultssupporting
confidence: 80%
“…Figures 9(a) and 9(b) depict the behaviour of Σ for runs that belong to groups 1 and 2 and group 3, respectively. The no-grid case, as described by run 1a, produces results that are similar to those of Buxton et al (2019), with an increase in anisotropy being observed near the wake boundary on the wake side of the interface. A very gradual increase in the anisotropy ratio FIGURE 9.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The intensityυ int is produced by an anisotropic field of motion characterized by large-scale engulfment events while the intensity υ int is produced by essentially isotropic small-scale fluctuations. It is then possible to argue that only the anisotropic part of the velocity field significantly contributes to the net propagation of scalars in agreement with a number of recent works (Cimarelli et al 2015(Cimarelli et al , 2021Buxton, Breda & Dhall 2019). Accordingly, we introduce the isotropy indicator…”
Section: Heuristic Refinement Of the Entrainment And Mixing Assumptionssupporting
confidence: 66%
“…This led to a spatial resolution (worst case) for the TPIV experiment of 11η at x/D e = 2, of 9η at x/D e = 10 and of 5η at x/D e = 25. These worst case figures are quoted assuming a Kolmogorov length scale computed from the bulk of the turbulent flow, although since the dissipation rate is known to reduce as the irrotational boundary is approached (van Reeuwijk & Holzner 2014;Buxton et al 2019) the "local" Kolmogorov length scale is around 20-25% larger hence the spatial resolution is accordingly finer than these worst-case scenarios. In terms of the longitudinal Taylor lengthscale, the spatial resolution ranged between 0.3λ f and 0.1λ f at the three locations studied.…”
Section: Spatial Resolutionmentioning
confidence: 99%